Activation of the aryl hydrocarbon receptor in inflammatory bowel disease: insights from gut microbiota - Hou, Jun-Jie; Ma, A-Huo; Qin, Yue-Hua (Frontiers in Cellular and Infection Microbiology, 2023)
Inflammatory bowel disease (IBD) is a chronic inflammatory intestinal disease that affects more than 3.5 million people, with rising prevalence. It deeply affects patients’ daily life, increasing the burden on patients, families, and society. Presently, the etiology of IBD remains incompletely clarified, while emerging evidence has demonstrated that altered gut microbiota and decreased aryl hydrocarbon receptor (AHR) activity are closely associated with IBD. Furthermore, microbial metabolites are capable of AHR activation as AHR ligands, while the AHR, in turn, affects the microbiota through various pathways. In light of the complex connection among gut microbiota, the AHR, and IBD, it is urgent to review the latest research progress in this field. In this review, we describe the role of gut microbiota and AHR activation in IBD and discussed the crosstalk between gut microbiota and the AHR in the context of IBD. Taken as a whole, we propose new therapeutic strategies targeting the AHR–microbiota axis for IBD, even for other related diseases caused by AHR-microbiota dysbiosis.